Digital Transformation of Services Midwifery : A Global Review of Telemedicine Use - Iffah, Uliy; Afrah, Rahmayani (Napande: Jurnal Bidan, 2025)
Background: Telemedicine has emerged as a key innovation in transforming global healthcare services, including midwifery practice. Advances in digital technology facilitate pregnancy monitoring, remote consultations, and maternal health education in a more efficient, timely, and cost-effective manner, thereby supporting Sustainable Development Goal (SDG) 3.1 to reduce maternal mortality. This article reviews the implementation of telemedicine in eight countries—Indonesia, India, Nigeria, Australia, the United Kingdom, Japan, Singapore, and the United States with an emphasis on its contribution to maternal health. Method: A literature review was conducted by analyzing scientific articles and books published between 2021 and 2025 that addressed midwifery, antenatal care, and maternal health outcomes. Result: In developing countries such as Indonesia, India, and Nigeria, telemedicine expands access to antenatal care, accelerates referrals, reduces geographic barriers, and enhances maternal health literacy through community-based digital platforms. In developed countries such as Australia, the United Kingdom, Japan, Singapore, and the United States, telemedicine focuses on health system integration, early detection of pregnancy complications, and optimizing service efficiency using advanced technologies, including artificial intelligence, big data analytics, telemonitoring, and wearable devices. Midwives play a pivotal role as direct care providers, clinical decision-makers, and intermediaries between digital platforms and patients. Conclusion: Telemedicine is not merely a temporary response to healthcare limitations in developing countries but also a catalyst for innovation, quality improvement, and equity in global midwifery services.